COVID-19, Companion Animals, Comparative Medicine, and One Health - Mobasheri, Ali (Frontiers in Veterinary Science, 2020)
The COVID-19 pandemic in 2020 has stimulated open collaboration between different scientific and clinical disciplines like never before. Public and private partnerships continue to form in order to tackle this unprecedented global challenge. This paper highlights the importance of open collaboration and cooperation between the disciplines of medicine, veterinary medicine and animal health sciences in the fight against COVID-19. Since the pandemic took the whole world by surprise, many existing drugs were rapidly repurposed and tested in COVID-19 clinical trials and some of the trials are revealing promising results, it is clear that the long-term solution will come in the form of vaccines. While vaccines are being developed, the antiviral agent Remdesivir (RDV, GS-5734) is being repurposed for use in human clinical trials but this is being done without acknowledging the significant efforts that went into development for treating cats with feline infectious peritonitis (FIP), a highly fatal immune-mediated vasculitis in cats. There are many other antiviral drugs and immune modulating treatments that are currently being trialled that have animal health origins in terms of discovery and clinical development. Closer collaboration between the animal health and human health sectors is likely to accelerate progress in the fight against COVID-19. There is much that we do not yet know about COVID-19 and its causative agent SARS-CoV-2 but we will learn and progress much faster if we increase interdisciplinary collaboration and communication between human and animal health researchers and taking a genuine “One Health” approach to this and other emerging viral pathogens.